Verb constructions in German and Dutch - Seuren, Pieter A. M.; Kempen, Gerard, 1943- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2003)
German and Dutch verb constructions show a rich array of syntactic phenomena that have so far been underexposed in the literature, despite the fact that they have proved to be a source of substantial problems in theoretical grammar. The cross-linguistic study of verb constructions and complementation has been dominated by views deriving from English or, for that matter, Latin. The German and Dutch complementation systems, however, feature several important properties that are missing from English but occur in many other languages. Well-known but only partially understood examples.